2016
DOI: 10.1002/jbm.a.35825
|View full text |Cite
|
Sign up to set email alerts
|

The component leaching from decellularized pericardial bioscaffolds and its implication in the macrophage response

Abstract: The extracellular matrix molecules remaining in bioscaffolds derived from decellularized xenogeneic tissues appear to be important for inducing cell functions conducting tissue regeneration. Here, we studied whether decellularization methods, that is, detergent Triton X-100 (TX) alone and TX combined with reversible alkaline swelling (STX), applied to bovine pericardial tissue, could affect the bioscaffold components. The in vitro macrophage response, subdermal biodegradation, and cell infiltration were also s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…In practice, a xenogeneic tissue is usually rendered acellular in order to minimize the immune response and rejection. This is typically accomplished by washing the tissue in a detergent, enzymatic or alkaline solution . In our current study, we used a decellularization protocol incorporating sodium hydroxide treatment which is considered effective in terms of prevention of Bovine Spongiform Encephalopathy transmission and has already proven itself suitable on the healthcare market .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In practice, a xenogeneic tissue is usually rendered acellular in order to minimize the immune response and rejection. This is typically accomplished by washing the tissue in a detergent, enzymatic or alkaline solution . In our current study, we used a decellularization protocol incorporating sodium hydroxide treatment which is considered effective in terms of prevention of Bovine Spongiform Encephalopathy transmission and has already proven itself suitable on the healthcare market .…”
Section: Discussionmentioning
confidence: 99%
“…The confluency and morphology of the cells were examined by CLSM and scanning electron microscopy (SEM) after 76 h in culture. For the CLSM analysis the cells were stained with a vital dye set, Calcein‐AM/EthD‐1 (LIVE/DEAD Viability/Cytotoxicity Kit for mammalian cells, Invitrogen), rinsed with PBS trice and observed by CLSM (see the details in Section 2.14) in order to record the green live cells and the red dead cells …”
Section: Methodsmentioning
confidence: 99%
“…Early studies evaluated dECM scaffolds in mice models and saw that exogenically implanted dECM induced acute inflammatory responses followed by chronic inflammation and ultimate graft necrosis and rejection . However, most recent studies using in vivo models of dECM therapy in rats and pigs saw little immune response with implanted xenogeneic scaffolds and showed that degradation products from variety of dECM materials activate constructive M2 macrophage phenotype . Mendoza‐Novelo et al showed that leaching of basement membrane components may be responsible for promoting faster macrophage stimulation and decreased inflammation.…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…Healing of a calvarial defect involves intramembranous ossification, which relies on direct differentiation of mesenchymal precursor cells into osteoblasts (Runyan & Gabrick, 2017). In the present study, we and GAG, all of which are well-known factors involved in cell adhesion and growth, which activated M2 macrophages and enhanced vascularization (Mendoza-Novelo et al, 2016). The action of ECM degradation components is another potential mechanism of ECM modulating tissue regeneration (Robb, Shridhar, & Flynn, 2017).…”
Section: Discussionmentioning
confidence: 63%